2023
DOI: 10.3390/nu15040915
|View full text |Cite
|
Sign up to set email alerts
|

Does Aging Have an Impact on Vitamin C Status and Requirements? A Scoping Review of Comparative Studies of Aging and Institutionalisation

Abstract: The global healthcare burden of an aging population continues to increase, with nearly a quarter of the total global burden of disease attributable to people aged ≥60 years. Older people are at greater risk of micronutrient deficiencies, including immune-supportive vitamin C, which is both a contributor to and a consequence of acute and chronic illnesses. However, whether healthy aging, per se, is associated with depleted vitamin C status and increased requirements for the vitamin is less certain. A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The effect of age on vitamin C requirements is less clear. Many studies have shown either no change or a decrease in vitamin C status in non-supplementing older people [ 10 , 11 ]. However, we recently reported that older people with lower vitamin C intakes may be at higher risk of insufficiency than younger people with similar intakes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of age on vitamin C requirements is less clear. Many studies have shown either no change or a decrease in vitamin C status in non-supplementing older people [ 10 , 11 ]. However, we recently reported that older people with lower vitamin C intakes may be at higher risk of insufficiency than younger people with similar intakes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of age on vitamin C requirements is less clear. Many studies have shown either no change or a decrease in vitamin C status in non-supplementing older people [10,11]. However, we recently reported that older people with lower vitamin C intakes may be at higher risk of deficiency than younger people with similar intakes [12].…”
Section: Introductionmentioning
confidence: 84%
“…Water-soluble vitamin deficiencies in older adults are common and present a significant health concern. Deficiencies in specific vitamins can result in various health issues, including megaloblastic anemia, mental status changes, and neurologic issues, and are related to rates of disorders common in older adults including Alzheimer's disease, type 2 diabetes, and cognitive decline [16][17][18][19][20].…”
Section: Water-soluble Vitaminsmentioning
confidence: 99%
“…Numerous studies have shown a lower vitamin C status and a higher prevalence of deficiency in individuals with various acute and chronic conditions, which are common among older people [19]. Although there is limited up-to-date information on the vitamin C status in older adults, data from the U.S. National Health and Nutrition Examination Surveys (NHANES 2003– 2006 and 2017–2018) indicate a higher vitamin C status and a lower or comparable prevalence of deficiency (<11 μmol/l) in people aged ≥60 compared to younger individuals.…”
Section: Water-soluble Vitaminsmentioning
confidence: 99%